Analisis Dikotomi Ruang dan Ekonomi di Kabupaten Sragen, Jawa Tengah - Nurfina Ike Ayuningtyas (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2020)
Sragen Regency can be divided into two areas based on its tiphologycal feature, that are the north and south part area of Bengawan Solo River. Those area not only have a different kind of soil based on tiphology but also have different degree of economic growth. The goals of this paper are to define which part of the Sragen Regency that has a high and low economic growth and what kind of policies that match with the problems of those areas. The method used in this paper is dividing the area of Sragen Regency into four part based on spatial feature and the economic growth. The result are, the area that have a high growth mostly located in south part of Bengawan solo and the area that have a low growth mostly located in north parth of Bengawan Solo.The policies for the low growth areas is driven to strengthen the main sector and to develop another promising sector that can be used to increase society income. While, the policies for the high growth areas mainly driven to find an indigenous product that can be used to determined the identity of the whole region, and also to make the final output resulted from the areas having a competitive ability against another region in the Central Java Province.